Are Central Africa′s Protected Areas Displacing Hundreds of Thousands of Rural Poor? - Curran Bryan; Sunderland Terry; Maisels Fiona; Oates John; Asaha Stella; Balinga Michael; Defo Louis; Dunn Andrew; Telfer Paul; Usongo Leonard; Loebenstein Karin; Roth Philipp (Conservation & Society, 2009)
An ongoing debate over the impacts of protected areas on rural communities in central Africa has become increasingly polarized in recent years, even as definitions of displacement have shifted from outright expulsion to economic dislocation precipitated by lost access to natural resources. Although forcible removal of communities to make way for the creation of National Parks has certainly occurred in the past in some parts of the world, we contend that not a single individual has been physically removed from any of the protected areas created in central Africa over the past decade, despite claims to the contrary of hundreds of thousands of "conservation refugees." Furthermore, we recognize that a scarcity of data precludes impartial evaluation of the potential impacts of economic displacement of local communities living adjacent to protected areas, and we call for a concerted effort by conservationists and the social scientists who criticize conservation efforts, in order to measure the effects of protected areas on livelihoods, and to work towards a more socially responsible conservation paradigm.